Megalopolis: An assay for the identification of the world urban mega-structures - Blanca Arellano Ramos; Josep Roca (European Regional Science Association (ERSA), 2015)
The urban development of the twentieth century can be characterized by rise of the metropolitanization process. However, especially since 1950, it has been producing a real change of scale in this growth: the infinite growth of metropolitan peripheries, encouraged by the process of urban sprawl, has increased the urbanization of rural environments in the interstices between cities and metropolitan areas. Previously isolated urban systems have been caught in the web of urbanization and generated new urban spaces characterized by increasing complexity. Megacities, intuited in the early twentieth century by precursors of contemporary urbanism (Geddes, 1915; Mumford, 1938), have come true (Gottmann, 1961). This paper, following the work begun by Florida et al (2008), uses the methodology of nighttime satellite images as a method for the delimitation of the megalopolis. This methodology allows the worldwide identification of 444,502 populated areas illuminated with sufficient intensity (64 on a scale of 256) for consideration of urban nature. 433 of these illuminated areas reach a population of over one million inhabitants, concentrating 2,537 million inhabitants, 37.8% of the population of the planet. 92 over 5 million represent the seeds of megalopolitan structures. And 30 structures, that we call proto-megas, exceed 15 million, reaching a population of 1,298,757,300 inhabitants, placing as strong candidates to be characterized as megalopolis. In the study presented here we identified 26 megacities with a population exceeding 20 million, concentrating 1,374,291,094 people in their environment. These megalopolis are distributed throughout the entire planet. Asia highlights the presence of 18 large agglomerations: 2 transnational (India-Pakistan and India-Bangladesh), 5 in India, 6 in China (5 in the continent and one in Taiwan), and 1 in Japan, Indonesia, Korea, Philippines and the Middle East. America (4 megalopolis), Europe (3 agglomerations) and Africa (1 agglomeration), demonstrate the global reach of the geography of the megalopolis. Only Oceania is free of such urban formations. It can be concluded that megacities are a new form of urban settlement that affects the entire planet. This fact is not a phenomenon exclusive of the first world versus what the pioneering work of Geddes, Mumford and Gottmann seemed to suggest. Latin America, Africa and especially Asia, are also protagonists of these new forms of occupation of space. Emerging urban territories that seem to make out a new economic and social order in which Europe and North America will no longer have the unique role of protagonist.
Keywords: R11; R12; 330; Megalopolis; Metropolis; Night Lights; Urban Agglomerations